Peningkatan Prestasi Belajar TIK Materi Menu dan Icon Microsoft Office Word Melalui Penerapan Metode Tutor Sebaya Pada Siswa Kelas VIII E Di SMP Negeri 2 Panggul Trenggalek - Wirawan, Surya Edi (Jurnal Simki Pedagogia, 2022)
The purpose of this research is to find out objectively the improvement of ICT learning achievement in Microsoft Office Word Menu and Icon Materials through the Application of Peer Tutor Methods in Class VIII E Semester 1 Students in the 2017/2018 Academic Year at SMP Negeri 2 Panggul Trenggalek. This research is a descriptive qualitative research type Classroom Action Research will be presented in the form of a cycle. Each cycle consists of four stages, namely (1) planning. (2) implementation or action, (3) observation, (4) reflection. This study uses one instrument, namely a test. The test instrument was used to collect achievement data. The results of this study in the first cycle have not reached classical completeness. There were 13 students who finished studying (50%). Completeness has not reached a minimum of 85%. Students who are smart but shy do not dare to appear to communicate their work so the research is continued to Cycle II. In cycle II it is good because it has reached completeness. There were 23 students who finished studying with a percentage of (88%). The mastery of classical learning has reached a minimum of 80%. Thus, it can be stated that the Tutor Model Cooperative Learning with the material of understanding Microsoft Office Word Menus and Icons takes place in an active, creative, effective, and fun way. Learning in Cycle II has been successful because minimum completeness can be achieved. The success of Cycle II was marked by the achievement of completeness of 88%.